(untitled) (Journal of the College of Basic Education, 2022)
This research was conducted at the College of Agriculture /Baghdad University during 2012 - 2013.The aims of this project were to evaluate three eggplant cultivars( Thurayya F1, Barshalona and Paris)for their resistance to Sclerotinia sclerotiorum (lib.) deBary in laboratory and greenhouse, In addition to develop a low-cost and high efficiency inoculation methods that can generate consistent results for screening the plants for resistance to sclerotinia stem rot . Three methods of inoculation were applied: the apical meristemes using plants of one month growth stage , inoculated with PDA mycelial pathogen plugs (5mm), detached leaf assay with PDA mycelial plugs (5mm) of pathogen and Oxalic acid (10mM). Lesion length , percentage of infected leaf area and peroxidase activity were measured .The results shown symptoms developed within 1 and 8 dayse after inoculation with both detached leaf assay and Oxalic acid and apical meristemes treatments respectively. Significant differences (P≤1%) among eggplant cultivars resistance to S. sclerotiorum were found. Thurayya F1 was the less sensitive to infection when produced lesion of 14.67mm in length and 0.6 % percentage of infected leaf area. Whereas, Barshalona and Paris produced 45 , 93.67 mm, and 1.39% , 1.79% respectively. Peroxidase activity estimated in the detached leaves infected was three and five times more fold in Thurayya F1 and Barshalona cultivar respectively compared to control, while no significant differences occurred in Paris cultivar